Characterization and potential lipid-lowering effects of lactic acid bacteria isolated from cats - Liang, Shukun; Kang, Yanhua; Zhao, Ya; Sun, Jintao; Wang, Xiumin; Tao, Hui; Wang, Zhenlong; Wang, Jinquan; Zhong, Yougang; Han, Bing (Frontiers in Microbiology, 2024)
Introduction This study aimed to study the characterization and the potential lipid-lowering effects of new isolated lactic acid bacteria from the feces of healthy adult cats. Methods We collected 85 cat fecal samples, isolated, screening lactic acid bacteria strains from samples, and investigated their in vitro and in vivo biological properties. Results A total of 221 lactic acid bacteria strains were isolated from 85 cat fecal samples. Sixteen strains with calcium dissolution rings greater than 1 mm were identified and selected for further characterization. Three lactic acid bacteria strains, Lactobacillus plantarum L-27-2, Pediococcus lactis L-14-1, and Enterococcus faecium, were identified as showing the most promising rates of cholesterol degradation (greater than 20%) and bacteriostatic radius (over 15 mm). These three strains exhibited robust growth and adherence to epithelial cells, along with adaptability to low pH (greater than 70%) and high bile salt conditions (greater than 60%), and remarkable cholesterol degradation and anti-pathogen activity. Sixteen mice were fed a high-fat diet (HFD) from 4 to 8 weeks of age, while a control group of the same size received a normal diet (ND). At 8 weeks of age, serum, feces and adipose tissue were collected. The results showed that, compared with mice fed an HFD diet alone, all mice fed an HFD diet plus lactic acid bacteria could decrease weight gain. P < 0.05 and the pathological changes of adipose tissue were alleviated. In addition, mice fed L-14-1 and F203 showed abdominal fat accumulation decreased (P < 0.05). Mice fed L-27-2 showed serum and liver triglyceride (TG) decreased (P < 0.05) and mice fed F203 showed serum high density lipoprotein cholesterol (HDL-C) increased (P < 0.01). mice fed L-27-2 and L-14-1 showed inflammatory cytokines (IL-6) was decreased (P < 0.01) Analysis of the fecal microbiota of mice fed these three lactic acid bacteria strains revealed alterations in the gut microbial community. There were common changes in intestinal microbes in mice fed these three lactic acid bacteria: (1) Bacteroides decreased; (2) Myxococcus increased; (3) Lachnoclostridium decreased. The microbes mentioned are all part of the core intestinal flora. Discussion This study provided three potential lactic acid bacteria for alleviating animal obesity and inflammation.